The Aligning Human Development Index with Maqāṣid al-Sharī’ah Principles - Muttaqin, Rizal (Journal of Economicate Studies, 2021)
This study reinterprets the Human Development Index (HDI) through the lens of Maqāṣid al-Sharī’ah, an Islamic framework emphasizing the preservation of religion, life, intellect, progeny, and wealth. While HDI focuses on quantifiable metrics such as health, education, and income, it omits spiritual, ethical, and communal dimensions vital to Islamic worldviews. Using qualitative methods and document analysis, this research explores the theoretical and operational compatibilities between HDI indicators and Maqasid objectives. The findings reveal that HDI’s core indicators align with key Maqasid principles but lack the ethical depth required for holistic development in Muslim contexts. By proposing an integrative framework, the study contributes a culturally grounded alternative to conventional development metrics. This model not only enhances HDI’s relevance in Islamic societies but also bridges empirical and spiritual paradigms, offering practical insights for policymakers, scholars, and development practitioners committed to faith-based governance.